Bromodomain protein 4 is a novel predictor of survival for gastric carcinoma - Zhu, Yixin (Oncotarget, 2017)
Expression of bromodomain protein 4 (BRD4) has been reported to predict a worse prognosis in solid tumors. However, its expression profile and prognostic value in gastric carcinoma (GC) remains unknown. Here we investigated BRD4 expression in GC and explored its association with patient survival. Tissue samples were obtained from 95 GC patients who underwent surgical resection to remove the primary tumor from January 2009 to December 2010. Immunohistochemistry was used to detect the expression of BRD4 in GC tissues and adjacent normal tissues. Kaplan–Meier survival curves and Cox proportional hazards regression were used to analyze the data of BRD4 expression profile and clinicopathological characteristics. Immunohistochemical analysis revealed BRD4 was overexpressed in GC tissue compared with adjacent normal tissue. BRD4 expression was significantly associated with TNM stage (p < 0.001), lymphatic permeation (p = 0.011), and vital status at the end of follow-up (p < 0.001). Kaplan–Meier survival curves and the log-rank test demonstrated that higher BRD4 expression was an adverse predictive factor for survival in GC. Multivariate analysis by Cox proportional hazards regression revealed that BRD4 expression was an independent worse prognostic factor in GC. In conclusion, BRD4 could act as a potential biomarker for prognostic assessment of GC.